Near infrared optical tomography using NIRFAST: Algorithm for numerical model and image reconstruction - Dehghani, Hamid; Eames, Matthew E.; Yalavarthy, Phaneendra K.; Davis, Scott C.; Srinivasan, Subhadra; Carpenter, Colin M.; Pogue, Brian W.; Paulsen, Keith D. (Communications in numerical methods in engineering, 2009)
Diffuse optical tomography, also known as near infrared tomography, has been under investigation, for non‐invasive functional imaging of tissue, specifically for the detection and characterization of breast cancer or other soft tissue lesions. Much work has been carried out for accurate modeling and image reconstruction from clinical data. NIRFAST, a modeling and image reconstruction package has been developed, which is capable of single wavelength and multi‐wavelength optical or functional imaging from measured data. The theory behind the modeling techniques as well as the image reconstruction algorithms is presented here, and 2D and 3D examples are presented to demonstrate its capabilities. The results show that 3D modeling can be combined with measured data from multiple wavelengths to reconstruct chromophore concentrations within the tissue. Additionally it is possible to recover scattering spectra, resulting from the dominant Mie‐type scatter present in tissue. Overall, this paper gives a comprehensive over view of the modeling techniques used in diffuse optical tomographic imaging, in the context of NIRFAST software package. Copyright © 2008 John Wiley & Sons, Ltd.